(1-i)x-(3-i)=0

Simple and best practice solution for (1-i)x-(3-i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1-i)x-(3-i)=0 equation:


Simplifying
(1 + -1i) * x + -1(3 + -1i) = 0

Reorder the terms for easier multiplication:
x(1 + -1i) + -1(3 + -1i) = 0
(1 * x + -1i * x) + -1(3 + -1i) = 0

Reorder the terms:
(-1ix + 1x) + -1(3 + -1i) = 0
(-1ix + 1x) + -1(3 + -1i) = 0
-1ix + 1x + (3 * -1 + -1i * -1) = 0
-1ix + 1x + (-3 + 1i) = 0

Reorder the terms:
-3 + 1i + -1ix + 1x = 0

Solving
-3 + 1i + -1ix + 1x = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 1i + -1ix + 3 + 1x = 0 + 3

Reorder the terms:
-3 + 3 + 1i + -1ix + 1x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 1i + -1ix + 1x = 0 + 3
1i + -1ix + 1x = 0 + 3

Combine like terms: 0 + 3 = 3
1i + -1ix + 1x = 3

Add '-1x' to each side of the equation.
1i + -1ix + 1x + -1x = 3 + -1x

Combine like terms: 1x + -1x = 0
1i + -1ix + 0 = 3 + -1x
1i + -1ix = 3 + -1x

Reorder the terms:
-3 + 1i + -1ix + x = 3 + -1x + -3 + x

Reorder the terms:
-3 + 1i + -1ix + x = 3 + -3 + -1x + x

Combine like terms: 3 + -3 = 0
-3 + 1i + -1ix + x = 0 + -1x + x
-3 + 1i + -1ix + x = -1x + x

Combine like terms: -1x + x = 0
-3 + 1i + -1ix + x = 0

The solution to this equation could not be determined.

See similar equations:

| 16-20f=-18f | | 5x+10-30=7x-500+150 | | 8m=-10+10m | | -h-10=h+6 | | 24.33333333+-2.333333333y+4x+23=180 | | 4(5(-8)+4)=9((-8)-8) | | -10+2y=8+4y | | 7(y+1)=6y-9 | | Ht=-16t^2+35+ho | | -8t=-3-5t | | 18y-405=99 | | 10-b=9b-10 | | 4c-2=8c-10 | | 2+8=-5(6x-2) | | -p=-7-2p | | 9x-38+21y-1=180 | | 3x+-5=7x+7 | | 8+g=-10-2g | | 24+0.20x=x | | 19=(x/8) | | 2r=7+3r | | 2x+14=3x-11 | | 2v-3-11v=-6(1+19v)+-6(-18v-11) | | -8d=8-6d | | 3n=2+5n | | 5x+14=4x | | C=37.03+0.25x | | 5k=-6+6k | | 3(m-15)=m-7 | | -q-10=-2q | | x+80+50+x+60=180 | | 28+5=44 |

Equations solver categories